ENHANCING VOCABULARY MASTERY IN GRADE X STUDENTS OF SMAN 1 NGAGLIK USING ENGLISH SONGS - Sukha, Prema Gupita; Yulia, Made Frida; Rahayu, Dewi (ELTR Journal, 2025)
Classroom Action Research (CAR) was aimed at improving the tenth MIPA 1 graders’ vocabulary mastery of SMAN 1 Ngaglik through English songs. Two cycles of classroom action research were conducted by integrating English songs into learning activities. Each cycle consisted of four stages: Planning, Acting, Observing, and Reflecting. In gathering the data, the researchers used two instruments; a pre-test and post-test, and a questionnaire. The pre-test and post-test scores were used to see the improvement in students’ vocabulary mastery. Subsequently, the questionnaire was used to find out the students’ perspectives on the use of songs in English class and the impact of English songs on the students’ vocabulary enrichment. The criteria for success were the average of the students’ post-test scores that should reach 80 and the existence of a positive impact on the students’ vocabulary mastery. The findings demonstrated an increase in the students’ post-test scores, whereby the average of those scores in the two cycles was beyond 80. The findings unveiled a positive perception of the English learning using songs and an increase in the students’ learning motivation in learning vocabulary. In conclusion, the use of English songs in learning had boosted the students' vocabulary mastery.